Becoming a reader: Significant social influences on avid book readers - Merga, Margaret (2017)
Â© 2017, American Library Association. All rights reserved. Understanding how social influences can foster avid book reader identification is a key research goal that warrants further investigation beyond a limited early-years lens. The authorâ€™s 2015 International Study of Avid Book Readers (ISABR) explored, as one of its key research questions, the influence positive social agents can have on avid book readers, relying on the retrospective reflections of respondents from a range of countries and supporting quantitative data to explore this research focus. Early influences were examined, with data suggesting that maternal instruction is the most prevalent source of early reading teaching. Most respondents (64.3 percent) were the recipients of positive influence from a social agent. Indirect avid reader influence, author influence, fostering access, shared social habit, reading for approval, recommendations and supporting choice, and exposure to reading aloud were recurring mechanisms of influence. The multiple mechanisms of influence identified constitute opportunities for engagement and subsequent intervention by literacy advocates, including librarians.